Ratiometric chemosensor for differentiation of TNP from other NACs using distinct blue fluorescence and visualization of latent fingerprints. Issue 3 (23rd December 2020) - Dhiman, Sukhvinder; Ahmad, Manzoor; Kumar, Gulshan; Luxami, Vijay; Singh, Prabhpreet; Kumar, Subodh
Abstract : Paper strips coated with the red-fluorescent probe DMAS-TP display a distinct blue fluorescence with 2, 4, 6-trinitrophenol and SiO2 @DMAS-TP NPs to visualize latent fingerprints up to level 3. Abstract : Chemosensors that demonstrate a ratiometric change in fluorescence are in demand, but are scarce for nitroaromatic compounds owing to fluorescence quenching by nitro-aromatic compounds (NACs). Here, we report that the aggregates of the tricationic fluorescent-red chemosensor DMAS-TP in buffer undergo simultaneous fluorescence quenching at 615 nm and an increase in fluorescence intensity between 510–540 nm, revealing an unprecedented ratiometric behaviour for 2, 4, 6-trinitrophenol (TNP). The amplified fluorescence change in the FI615nm /FI521nm ratio from 57.67 to 30.18 (∼50%) with only 0.2 equivalents (2 μM) of TNP allows determination of TNP at a concentration as low as 2 nM. Paper strips coated with DMAS-TP differentiate TNP from other NACs through a fluorescence colour change from pink-red to blue with TNP only and provide unprecedented recognition of TNP from other NACs. In comparison to the only reported ratiometric probe for TNP, DMAS-TP provides advantages in terms of its usability in water and lower limit of detection. Furthermore, DMAS-TP adsorbed on silica nano-particles (10–20 nm) reveals a high fluorescence quantum yield ( ϕ = 10.72%) with an emission maxima at approximately 615 nm, in the far-red region. These fluorescent silica nanoparticles NPs can be used to visualize latent fingerprints on a variety of substrates such as aluminium foil, metal sheets, coins, ceramic tiles and so on, with a high resolution and could be used in modern forensic applications.